2019
DOI: 10.1039/c8mh01264d
|View full text |Cite
|
Sign up to set email alerts
|

Two-dimensional arrays self-assembledviainterference of concentration modulation waves in drying solutions

Abstract: Self-assembly of patterned nanostructures in solution-processed thin films with single phase polymers is successful.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 37 publications
1
2
0
Order By: Relevance
“…where G'' is the second derivative of the free energy of solution system with respect to composition, and k is the 'square gradient' parameter. By taking k~0.05-0.4 (Å 2 molcm -3 ) and -G''~10 -7 -10 -5 (molcm -3 ), 36,37 one can estimate sn ~0.1-3 m, which agrees with our experiment.…”
Section: Pattern Formation Mechanism and Simulationssupporting
confidence: 89%
“…where G'' is the second derivative of the free energy of solution system with respect to composition, and k is the 'square gradient' parameter. By taking k~0.05-0.4 (Å 2 molcm -3 ) and -G''~10 -7 -10 -5 (molcm -3 ), 36,37 one can estimate sn ~0.1-3 m, which agrees with our experiment.…”
Section: Pattern Formation Mechanism and Simulationssupporting
confidence: 89%
“…Li et al 108 demonstrated the pattern-formation process that can produce 2D arrays of sub-micrometric size through the principle that is similar to optical interference lithography, which is based on the interference between two beams, split from a coherent laser source, forms a standing wave that is recorded on a photoresist coated wafer to fabricate nanoscale pattern. 109,110 However, the solution based pattern-formation process using two waves are formed through the adjustment of the concentration in a dry solution next to the three-phase line or contact line.…”
Section: Self-assemble Direct Patternsmentioning
confidence: 99%
“…Top-down techniques face problems in the fabrication of three dimensions (3D) and multi-material nanostructures, limiting the enhancement research 5 . While bottom-up techniques, such as selfassembly methods, show advantages over shape control and multi-composite synthesis, benefiting from the chemically synthesized nanoparticles [27][28][29][30][31][32][33] . Nevertheless, the nanostructures using bottom-up approaches usually feature random particle distribution.…”
mentioning
confidence: 99%